2021
DOI: 10.2147/dmso.s295757
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Epidemiological Analysis of Prognostic Nutritional Index Associated with Diabetic Retinopathy

Abstract: Purpose Prognostic nutritional index (PNI) is an effective tool to evaluate the nutritional conditions and predict prognosis, but clinical data are limited for the use of PNI in diabetic retinopathy (DR). This study aimed to investigate the relationship of PNI with the prevalence and severity of DR in patients with type 2 diabetes mellitus (T2DM). Patients and Methods This cross-sectional analysis enrolled 1023 individuals with T2DM hospitalized between 2017–2020. PNI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The authors included 1023 DM patients in the study. As a result of the study, they found that low PNI values were an independent predictor of retinopathy, its presence and severity in patients with DM [Yang 2021]. In our current study, we determined the PNI value in patients with insulin-dependent diabetes as an independent predictor of postoperative AKI.…”
Section: E654mentioning
confidence: 77%
“…The authors included 1023 DM patients in the study. As a result of the study, they found that low PNI values were an independent predictor of retinopathy, its presence and severity in patients with DM [Yang 2021]. In our current study, we determined the PNI value in patients with insulin-dependent diabetes as an independent predictor of postoperative AKI.…”
Section: E654mentioning
confidence: 77%
“…None of the previous studies on sALB and DR excluded patients with co-morbidity of DR and DKD. 9,34 The occurrence of this situation in our study may be related to the insufficient sample size of patients in the DR only group because some patients with DR are divided into the DR + DKD group, and the sALB level in the DR + DKD group is significantly lower than that in the DKD only, DR only, and control group. However, patients with DR and DKD comorbidities may have different pathophysiological mechanisms from those with DR or DKD alone.…”
mentioning
confidence: 73%
“… 6 Oxidative stress, as an “important promoter” of occurrence and development of diabetic microvascular complications, 7 so in recent years, the relationship between sALB and diabetic microvascular complications has attracted attention. Studies have found that hypoalbuminemia is associated with poorer renal prognosis in patients with diabetic nephropathy; 8 and sALB in non-proliferative DR and vision-threatening DR was significantly lower than that in patients without DR, and the prognostic nutritional index calculated based on sALB was inversely and independently correlated with the severity and prevalence of DR. 9 However, both DKD and DR are microvascular complications of diabetes, and to our knowledge, their association with sALB has not been comprehensively simultaneously analyzed in one study.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the PNI paradigm can be traced back to a study by Buzby et al In their purview [ 23 ], the assessment of gastrointestinal surgery risks incorporated the appraisal of peripheral blood lymphocyte counts and serum albumin levels, emerging as indicators of systemic immunonutrition and inflammatory status. Numerous studies have shown that PNI can be used as a predictive or prognostic biomarker for various cancers such as gastric cancer, hepatocellular carcinoma, nasopharyngeal carcinoma, colorectal cancer [ [24] , [25] , [26] , [27] ], heart failure, acute pancreatitis, and diabetic retinopathy, among others [ 15 , [28] , [29] , [30] ].…”
Section: Discussionmentioning
confidence: 99%